Postural adjustments during single leg droplanding in subjects with chronic ankle unstability - Sousa, Andreia (2023)
Chronic ankle instability (CAI) involves deregulation of postural control mechanisms and is estimated to occur in 70% of the individuals after ankle SPRAIN.